KETERAMPILAN KERJA ILMIAH SISWA SMA PADA MATERI LAJU REAKSI MENGGUNAKAN MODEL PEMBELAJARAN INKUIRI TERBIMBING - Hartati Widyaningsih, Fransiska Tri; Sahputra, Rachmat; Enawaty, Eny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this study was to describe the profile of students's scientific work skills before and after being applied to guided inquiry learning models in the "reaction rate" material and determine the differences in scientific work skills of students in Pontianak 8 State High School 2018/2019 academic year. This study used a pre-experimental method with one group pretest-posttest research design. The sample in this study were students of class XI MIPA 2 with the determination of the sample using purposive sampling technique. Data collection uses measurement techniques and direct communication techniques. After data analysis, the results of the pretest showed that the scientific work skills of students were in the unskilled, less skilled, category at 45.5%; 54.5%. Then the posttest results showed that the scientific work skills of students were in the category of less skilled, skilled, highly skilled in a row of 3.03%; 24.24%; 72.73%. Wilcoxon test results have shown there are differences in scientific work skills before and after learning, it can be concluded that students' scientific work skills increase after applied guided inquiry learning models.Â Keywords: scientific work skills, guided inquiry, reaction rate